2016
DOI: 10.1002/ptr.5565
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic Acid Attenuates Osteoclastogenesis by Downregulating JNK/c‐Fos/NFATc1 Signaling and Prevents Inflammatory Bone Loss in Mice

Abstract: Protocatechuic acid (PCA) plays a critical role in nutritional metabolism; it is a major metabolite of anthocyanins, which are flavonoids with a range of health benefits. PCA has a variety of biological activities including anti-oxidant, antiinflammatory, anti-apoptosis, and anti-microbial activities. However, the pharmacological effect of PCA, especially on osteoclastogenesis, remains unknown. We examined the effect of PCA on receptor activator of NF-κB ligand (RANKL)-induced osteoclast differentiation and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…In vivo, PCA was shown to have a protective effect against LPS-induced bone loss. PCA was also found to downregulate the expression of osteoclastogenesis-related genes, including DC-STAMP and b3-integrin (Park et al, 2016b).…”
Section: Anti-diabetes Activitymentioning
confidence: 93%
“…In vivo, PCA was shown to have a protective effect against LPS-induced bone loss. PCA was also found to downregulate the expression of osteoclastogenesis-related genes, including DC-STAMP and b3-integrin (Park et al, 2016b).…”
Section: Anti-diabetes Activitymentioning
confidence: 93%
“…In addition, the RANKL-mediated signaling pathways including mitogen-activated protein kinases, nuclear factor κ B, and cyclooygenase-2 could be attenuated by PCA treatment [ 21 ]. Park et al have shown that PCA inhibits RANKL-induced osteoclast differentiation in mouse bone marrow macrophages and lipopolysaccharide-induced inflammatory bone loss in mice [ 24 ]. In contrast, Rivera-Piza et al suggested in 2017 that PCA might enhance osteogenesis in C3H10T1/2 and 3T3-L1 cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have demonstrated for the first time that We attempted to define the underlying mechanism for DAP's antiosteoclastogenic effect in vitro by exploring the effects of DAP (Deepak, Kruger, & Coetzee, 2016;Miyazaki et al, 2000;Park et al, 2016).…”
Section: Dap Affects Rankl-induced Erk Phosphorylation and Nfatc1 Amentioning
confidence: 90%